Intravascular Catheter-Related Bloodstream Infection. (July 2013) - Shah, Harshal; Bosch, Wendelyn; Thompson, Kristine M.; Hellinger, Walter C.
Intravascular catheters required for the care of many hospitalized patients can give rise to bloodstream infection, a complication of care that has occurred most frequently in intensive care unit (ICU) settings. Elucidation of the pathogenesis of catheter-related bloodstream infections (CRBSIs) has guided development of effective diagnostic, management, and prevention strategies. When CRBSIs occur in the ICU, physicians must be prepared to recognize and treat them. Prevention of these infections requires careful attention to optimal catheter selection, insertion and maintenance, and to removal of catheters when they are no longer needed. This review provides a succinct summary of the epidemiology, pathogenesis, and microbiology of CRBSIs and a review of current guidance for the diagnosis, management, and prevention of these infections.